Psychedelic therapy : a revolutionary approach to restoring your mental health and reclaiming your life - Van Derveer, Will; Kurlander, Keith (Shambhala, 2026)
"This book explores the potential for psychedelic-assisted therapy (PAT) to revolutionize modern mental health care by addressing the root causes of trauma"-- Provided by publisher.